# Calculator search results

Formula
Number of solution
Relationship between roots and coefficients
Graph
$y = 2 x ^ { 2 } - 72$
$y = 0$
$x$Intercept
$\left ( - 6 , 0 \right )$, $\left ( 6 , 0 \right )$
$y$Intercept
$\left ( 0 , - 72 \right )$
Minimum
$\left ( 0 , - 72 \right )$
Standard form
$y = 2 x ^ { 2 } - 72$
$2x ^{ 2 } -72 = 0$
$\begin{array} {l} x = 6 \\ x = - 6 \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = \color{#FF6800}{ 0 }$
$x ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
 Move the constant to the right side and change the sign 
$x ^ { 2 } = \color{#FF6800}{ 36 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 36 }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 36 } }$
$\color{#FF6800}{ x } = \pm \sqrt{ \color{#FF6800}{ 36 } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 6 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 6 }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ 6 } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{array}$
$\begin{array} {l} x = 6 \\ x = - 6 \end{array}$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = 0$
 Bind the expressions with the common factor $2$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 36 } \right ) = 0$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 36 } \right ) = \color{#FF6800}{ 0 }$
 Divide both sides by $2$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = \color{#FF6800}{ 0 }$
$x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 0 } \pm \sqrt{ 0 ^ { 2 } - 4 \times 1 \times \left ( - 36 \right ) } } { 2 \times 1 }$
 0 has no sign 
$x = \dfrac { \color{#FF6800}{ 0 } \pm \sqrt{ 0 ^ { 2 } - 4 \times 1 \times \left ( - 36 \right ) } } { 2 \times 1 }$
$x = \dfrac { 0 \pm \sqrt{ \color{#FF6800}{ 0 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 36 \right ) } } { 2 \times 1 }$
 The power of 0 is 0 
$x = \dfrac { 0 \pm \sqrt{ \color{#FF6800}{ 0 } - 4 \times 1 \times \left ( - 36 \right ) } } { 2 \times 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 0 \pm \sqrt{ 0 - 4 \times 1 \times \left ( - 36 \right ) } } { 2 \times 1 } }$
 Organize the expression 
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 0 \pm \sqrt{ 144 } } { 2 \times 1 } }$
$x = \dfrac { 0 \pm \sqrt{ \color{#FF6800}{ 144 } } } { 2 \times 1 }$
 Organize the part that can be taken out of the radical sign inside the square root symbol 
$x = \dfrac { 0 \pm \color{#FF6800}{ 12 } } { 2 \times 1 }$
$x = \dfrac { 0 \pm 12 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
 Multiplying any number by 1 does not change the value 
$x = \dfrac { 0 \pm 12 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 0 \pm 12 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 0 + 12 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 0 - 12 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 0 } + 12 } { 2 } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
 0 does not change when you add or subtract 
$\begin{array} {l} x = \dfrac { 12 } { 2 } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 12 } { 2 } } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 6 } { 1 } } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 6 } { 1 } } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
 Reduce the fraction to the lowest term 
$\begin{array} {l} x = \color{#FF6800}{ 6 } \\ x = \dfrac { 0 - 12 } { 2 } \end{array}$
$\begin{array} {l} x = 6 \\ x = \dfrac { \color{#FF6800}{ 0 } - 12 } { 2 } \end{array}$
 0 does not change when you add or subtract 
$\begin{array} {l} x = 6 \\ x = \dfrac { - 12 } { 2 } \end{array}$
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ \dfrac { - 12 } { 2 } } \end{array}$
 Do the reduction of the fraction format 
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ \dfrac { - 6 } { 1 } } \end{array}$
$\begin{array} {l} x = 6 \\ x = \dfrac { - 6 } { \color{#FF6800}{ 1 } } \end{array}$
 If the denominator is 1, the denominator can be removed 
$\begin{array} {l} x = 6 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \end{array}$
 2 real roots 
Find the number of solutions
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = \color{#FF6800}{ 0 }$
 Determine the number of roots using discriminant, $D=b^{2}-4ac$ from quadratic equation, $ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \color{#FF6800}{ 0 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 72 } \right )$
$D = \color{#FF6800}{ 0 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times \left ( - 72 \right )$
 The power of 0 is 0 
$D = \color{#FF6800}{ 0 } - 4 \times 2 \times \left ( - 72 \right )$
$D = \color{#FF6800}{ 0 } - 4 \times 2 \times \left ( - 72 \right )$
 0 does not change when you add or subtract 
$D = - 4 \times 2 \times \left ( - 72 \right )$
$D = \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 72 } \right )$
 Multiply the numbers 
$D = \color{#FF6800}{ 576 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 576 }$
 Since $D>0$ , the number of real root of the following quadratic equation is 2 
 2 real roots 
$\alpha + \beta = 0 , \alpha \beta = - 36$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 72 } = \color{#FF6800}{ 0 }$
 In the quadratic equation $ax^{2}+bx+c=0$ , if the two roots are $\alpha, \beta$ , then it is $\alpha + \beta =-\dfrac{b}{a}$ , $\alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 0 } { 2 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 72 } { 2 } }$
$\alpha + \beta = - \color{#FF6800}{ \dfrac { 0 } { 2 } } , \alpha \beta = \dfrac { - 72 } { 2 }$
 If the numerator is 0, it is equal to 0 
$\alpha + \beta = - \color{#FF6800}{ 0 } , \alpha \beta = \dfrac { - 72 } { 2 }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ 0 } , \alpha \beta = \dfrac { - 72 } { 2 }$
 0 has no sign 
$\alpha + \beta = \color{#FF6800}{ 0 } , \alpha \beta = \dfrac { - 72 } { 2 }$
$\alpha + \beta = 0 , \alpha \beta = \color{#FF6800}{ \dfrac { - 72 } { 2 } }$
 Reduce the fraction 
$\alpha + \beta = 0 , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ 36 }$
 그래프 보기 
Graph
Solution search results
Other